Analisis Pengaruh Motivasi Konsumen, Persepsi Kualitas, dan Sikap Konsumen Terhadap Keputusan Pembelian PC Tablet iPad (Studi Pada Konsumen iPad di Semarang) - Ferdian Ario Sasongko; Imroatul Khasanah (Conference In Business, Accounting, And Management (CBAM), 2012)
This research was based by the increasing number of PC Tablet on the market. One of them is iPad. Where is iPad always been a market leader since its first launch in 2010, although the number of competitor always rise. The aim of the research is to analyze the influence of consumer motivation, perceived quality, and consumer attitudes toward buying decision of the PC Tablet iPad. The result shows that consumers motivation, perceived quality, and consumer attitudes have significant relationship with buying decision. Perceived quality has higher influences for buying decisions than perceived quality and consumer attitudes.Keywords: Buying Decision, Consumer Motivation, Perceived Quality, Consumer Attitudes